DAMPAK BANTUAN BENIH JAGUNG PROGRAM TJPS TERHADAP PRODUKSI JAGUNG DI DESA BAUMATA KECAMATAN TAEBENU KABUPATEN KUPANG - Sakinah, Anis A; Nikolaus, Serman; Darlen, Maria F (Undana Press, 2023)
One of the important elements in agricultural cultivation is seed. The use of superior seeds can be a determining factor for the success of agricultural cultivation. It is noted that in the last two years corn production in Taebenu sub-district has increased. One of the factors that led to an increase in corn production in Taebenu District was the assistance of seeds through the Cattle Harvest Corn Planting (TJPS) program. So this study aims to determine the characteristics of corn seed assistance, production and income before and after the seed assistance program, and the significance of differences in corn production and income before and after the seed assistance program. This research was conducted by interviewing 51 sample farmer respondents. Data analysis used the Wilcoxon test, looking for the average value of production and income, and narrating the characteristics of the seed assistance. The results showed that corn seed assistance through the TJPS program received by farmers was in the form of hybrid varieties of corn seeds with a growth capacity of 80-85% as much as 30 kg/group of farmers which were distributed once per corn planting period. This assistance was distributed through farmer groups and then distributed to each member according to the area of ​​land cultivated. TJPS assistance has a positive impact on farmers' production and income. After the seed assistance, the average production increased by 2,856.86 (19.7%) kg from before and income increased by IDR 7,353,956.9 (59.7%) from before.